PENGARUH KUALITAS PELAPORAN KEUANGAN, DEBT MATURITY, DAN FREE CASH FLOW TERHADAP EFISIENSI INVESTASI DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Hanyfah Arifia; Febri Harianto Purbady; Syu’ban Nuradila; Desy Purwasih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to examine the effect of financial reporting quality, debt maturity and free cash flow on investment efficiency with the moderating effect of good corporate governanncr. The population of this research is Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. This research is quantitative research with an associative method. The data used in this research is secondary data. This research was conducted with the help of Eviews version 9.0. The research method used is multiple linear regression analysis of panel data and moderated regression analysis. The results of this study indicate that the quality of financial reporting, debt maturity and free cash flow simultaneously have a positive effect on investment efficiency. It partially shows that the quality of financial reporting and debt maturity have no effect on investment efficiency, and free cash flow has a negative effect on investment efficiency. Then good corporate governance does not moderate the relationship between financial reporting quality, debt maturity and free cash flow on investment efficiency.